Distribution and Existence of Books in the Religious Department and Educational Institutions of Yakutia (1638—1917) - Svetlana I. Boitunova; Светлана Иннокентьевна Бойтунова (Bibliotekovedenie [Library and Information Science], 2017)
The article presents the history of book occurrence in Yakutia, gives a brief review of the litera-ture on this subject, and reveals the first information and facts on the existence of books in this region. The author analyzes the list of service books, sent to the Lensky Ostrog in 1638, which reflects the earliest evidence of book emergence, the facts of origination of private books sale-purchase and possession, the circle of owners, etc. The article reviews the mechanisms of book collections formation of the Religious Department, analyzes the registers of the books obligatory for ordering by the decree of the Ecclesiastical Consistory and the regulations for opening field churches with books for the people with a nomadic way of life. The author characterizes the churches of Yakutia as educational and spiritual centers of targeted dissemination and distribution of books, notes the features of mandatory distribution in the churches of Yakutia and the origins of formation of book orders from private booksellers by the Religious Department.A significant place in the article is given to the educational institutions of Yakutia of the period under review: their sorts, types, forms of ownership, geographic location, and a list of the bookselling firms that collaborated with both spiritual and secular educational institutions. The geography of orders, the orga-nization and the quantitative and qualitative composition of the collections of educational and teachers’ libraries, the acquisition profiles via the printed catalogs of bookstores and the circulars, as well as the formation of book collections of the educational institutions of Yakutia are of great interest. В статье представлена история проникновения книги в Якутию, дан краткий обзор источников по теме, выявлены первые сведения и факты о бытовании книги в крае. В поле внимания автора находится перечень богослужебных книг, отправленных в Ленский острог в 1638 г., отразивший наиболее ранние свидетельства появления книги, факты зарождения купли-продажи и ...